On a Class of Eigenvalue Elliptic Systems in Fractional Sobolev Spaces with Variable Exponents (Journal of Nonlinear Modeling and Analysis, 2025)
In this work, we consider a class of eigenvalue elliptic systemsinvolving the fractional $(p(x, .), q(x, .))$-Laplacian operators. Our main toolsare based on Mountain Pass Theorem and Fountain Theorem.